Implementation of Sound Effects and Voice Over Techniques in Creating Motion Graphic “Budidaya Ayam Kampung Unggul Balitbangtan” - Ihsanul Hadi; Amata Fami; Benito Ibrahim Delano (Universitas Pendidikan Indonesia (UPI), 2023)
In the current era of technological advances used to provide information has grown very rapidly. Various kinds of media are used, one of them is Motion Graphic. The motion graphic entitled